COVID19: a case report of thrombus in transit. Issue Volume 4:Issue FI1(2020)Special Issue (17th June 2020) - Janus, Scott E; Hajjari, Jamal; Cunningham, Michael J; Hoit, Brian D
Abstract: Background: The global pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused significant morbidity and mortality, not only through devastating lung injury, but also due to multiple malfunctions in the cardiovascular system. The primary aetiology is believed to be mediated through lung alveolar injury; however, a few published reports have linked SARS-CoV-2 to significant organ dysfunction, venous thrombo-embolism, and coagulopathy. In view of the fact that the utility of tissue plasminogen activator in this population is not well studied, we present this case of rapid improvement in oxygenation after successful lytic therapy for thrombus in transit in this patient with SARS-CoV-2. Case summary: We discuss a patient admitted with SARS-CoV-2 pneumonia. Due to the development of dramatic hypoxia, he underwent echocardiography which demonstrated extensive thrombus in transit. He received successful thrombolytic therapy with tissue plasminogen activator, with subsequent improvement in oxygenation. The patient was successfully discharged home on 2 L of oxygen via nasal cannula, and continues to improve at follow-up with his cardiologist and primary care physician. Conclusion: This case not only highlights embolic causes of hypoxia in SARS-CoV-2, but demonstrates the important utility of an echocardiogram and tissue plasminogen activator in this population.